PERANCANGAN MEDIA SMART BOOK: UPAYA MENGATASI KESULITAN ANAK TUNANETRA MEMBACA AKSARA ARAB - Cela Petty Susanti; Dwi Purwati; Rosendah Dwi Maulaya (Jurnal Muara Pendidikan, 2023)
In Islam there is an obligation to study, especially studying religion. In Indonesia, studying through tiered education has been guaranteed by the state. However, the fact that visually impaired children have learning difficulties so as not get the same educational rights as normal children initiated the authors to conduct this study. With limited vision, such visually impaired children are deprived of the right to learn. Therefore, in this study, the author tried to design a learning media design whose function is to make it easier for visually impaired children to learn to recognize hijaiyah letters. The purpose of this study is to provide an overview of the design of hijaiyah learning media, namely the smart book. The substance taken is that the hijaiyah letter is based on the reason that religious education for generations of Muslims is very important. There is also in religious education that must be mastered first is the main source, namely the Qur'an. Thus, recognizing the hijaiyah letters, the basis for reading the Qur’an, is important to master first. The preparation of this paper uses the prototype method of literature study which is solving community problems by tracing the sources of writings that have been made. The design created was developed with a pop-up book-based media that can be palpable and identified. The digital technology components used are voice recognition, raspberry pi 4, loudspeakers, and Braille letterboards. The advantages of the smart book besides the object that appears, when touched it will produce the sound of the name of the object, there is a correct way of reading according to the makhorijul letters, and there are tones in the reading. It is predicted that with learning media that is simple in design, it will be able to achieve learning goals effectively and efficiently. So, visually impaired children can learn easily and fun. Therefore, the development of related media according to the author needs to be disseminated to children with visual impairments to support their learning activities.